Pulmonary Function Tests in Clinical Practice - Altalag, Ali; Road, Jeremy; Wilcox, Pearce (Springer London : Imprint: Springer, 2009)
Pulmonary Function Tests in Clinical Practice is an unique book providing a simplified approach to interpreting most diagnostic tests in the field of respiratory medicine. Easy to understand and practical, it contains more than 125 illustrated diagrams and over 50 tables with essential information that summarize the various diagnostic tests and interpretative approaches in a simple and understandable fashion. Of special note are chapters on exercise testing and diagnostic tests for sleep disorders, the latter a new and emerging field. The book assists residents and fellows in internal medicine, pulmonology, allergology and critical care by explaining the key information obtained from lung volume measurement and increases understanding of pulmonary function tests within the modern diagnostic armamentarium.